Schooling: Knowledge, Perception and Practices of Parents - Bharati, Saraswoti; Takao, Hosokawa (Journal of Education and Research, 2010)
This paper aims to provide an insight in policy making for further development in primary education sector. It is based on a field study conducted in Talku Dudhechaur village during September – October, 2008 to analyze the role of parents in schooling in rural area. The study showed that in spite of low economic and education level of the family, there is an increased demand and desire for schooling. However, about half of the parents’ attitude towards schooling is still negligent, due to lack of willingness and determination. This confirmed that the establishment of free primary education is not a sufficient solution. Instead making primary education compulsory and involving parents in school education more closely is an urgent need. In addition, compulsory birth registration and implementing modest laws and duty are also required to ensure the change in schooling pattern. DOI: http://dx.doi.org/10.3126/jer.v2i0.7622 Journal of Education and Research Vol. 2, 2010 p.44-51